PENGARUH PELATIHAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP PROFESIONALISME PEGAWAI DI KPP PRATAMA BANGKALAN - Arifin Kamil; Sundjoto; Sri Rahayu (MANAJEMEN DEWANTARA, 2023)
This study aims to examine the influence of job training, work discipline, and organizational commitment on employee professionalism at work. The sample in this study were 79 employees at the Bangkalan Tax Service Office. The analytical tool used in this study is multiple linear regression. The data processing application uses SPSS version 22. The results show that simultaneously by using the F test, the variables between job training, work discipline, and organizational commitment affect employee professionalism, while partially by using the t test, job training variables, work discipline, and organizational commitment has a significant effect on employee professionalism at KPP Pratama Bangkalan